Good-Bye - Ralph Waldo Emerson (Տպարան Սրբոյ Յակոբեանց)
Մնաս Բարով / Էմըրսըն Ռալֆ Ուալտօ։ Թարգմ.՝ Շէն-Մահ։ Ագնլերէն-հայերէն զուգադիր։
Keywords: Language and Literature; Translation and interpretation; Literature